Does responsiveness to arbuscular mycorrhizal fungi depend on plant invasive status?. Issue 16 (10th July 2017) - Reinhart, Kurt O.; Lekberg, Ylva; Klironomos, John; Maherali, Hafiz
Abstract: Differences in the direction and degree to which invasive alien and native plants are influenced by mycorrhizal associations could indicate a general mechanism of plant invasion, but whether or not such differences exist is unclear. Here, we tested whether mycorrhizal responsiveness varies by plant invasive status while controlling for phylogenetic relatedness among plants with two large grassland datasets. Mycorrhizal responsiveness was measured for 68 taxa from the Northern Plains, and data for 95 taxa from the Central Plains were included. Nineteen percent of taxa from the Northern Plains had greater total biomass with mycorrhizas while 61% of taxa from the Central Plains responded positively. For the Northern Plains taxa, measurable effects often depended on the response variable (i.e., total biomass, shoot biomass, and root mass ratio) suggesting varied resource allocation strategies when roots are colonized by arbuscular mycorrhizal fungi. In both datasets, invasive status was nonrandomly distributed on the phylogeny. Invasive taxa were mainly from two clades, that is, Poaceae and Asteraceae families. In contrast, mycorrhizal responsiveness was randomly distributed over the phylogeny for taxa from the Northern Plains, but nonrandomly distributed for taxa from the Central Plains. After controlling for phylogenetic similarity, we found no evidence that invasive taxa responded differently to mycorrhizas than other taxa. Although it is possible that mycorrhizal responsiveness contributes to invasiveness in particular species, we find no evidence that invasiveness in general is associated with the degree of mycorrhizal responsiveness. However, mycorrhizal responsiveness among species grown under common conditions was highly variable, and more work is needed to determine the causes of this variation. Abstract : After controlling for phylogenetic similarity, we found no evidence that invasive taxa responded differently to mycorrhizas than other taxa. Although it is possible that mycorrhizal responsiveness contributes to invasiveness in particular species, weak mycorrhizal responsiveness may not be a general mechanism of plant invasion.